2016
DOI: 10.1097/acm.0000000000001056
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Mentoring Interventions for Underrepresented Minorities

Abstract: Purpose To conduct a randomized controlled trial (RCT) to evaluate the effects of different mentoring interventions on the basic psychological need satisfaction of underrepresented minorities and women in academia. Method Participants were 150 mentor/protégé dyads from three academic medical centers and eight other colleges and universities in western and central New York, randomized from 2010–2013 into: mentor training (using principles of self-determination theory); peer mentoring for protégés; mentor trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 30 publications
0
62
0
Order By: Relevance
“…Other mentorship studies have found that time must be set aside for regular mentorship to occur and that the time to do mentorship should be recognized in annual activity reviews for senior faculty 10 . Finally, mentors require formal training or coaching in order to standardize a mentorship program and ensure that mentees are receiving similar help and advice 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Other mentorship studies have found that time must be set aside for regular mentorship to occur and that the time to do mentorship should be recognized in annual activity reviews for senior faculty 10 . Finally, mentors require formal training or coaching in order to standardize a mentorship program and ensure that mentees are receiving similar help and advice 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Structured research training programs help mentors, research teams, and thesis committees understand the challenges that trainees are facing, particularly challenges that emerge from the intersection of a trainee's unique racial or cultural background and the traditional research training culture (Museus and Liverman, 2010;Packard, 2015;Godwin et al, 2016;Layton et al, 2016;Carver et al, 2017;Research Triangle International, 2018). Without program support, trainees whose experiences and values do not align with traditional research culture may struggle to develop the social and cultural capital they need to successfully navigate and persist in research (Bauer and Bennett, 2003;Hurtado et al, 2008;Lewis et al, 2016;Mau, 2016;Carver et al, 2017). The Entering Research curriculum is a collection of activities and resources that develop the skills and knowledge undergraduate and graduate research trainees need to navigate the research culture and succeed in research.…”
Section: Introductionmentioning
confidence: 99%
“…As national attention on effective research mentoring in science and medicine disciplines has heightened [1][2][3][4][5][6][7], so too has recognition that mentors and mentees can benefit from structured training in how to initiate and sustain high-quality research mentoring relationships [8][9][10][11]. A variety of approaches to research mentor development have been reported [12][13][14][15][16][17][18][19][20], but one of the most widely disseminated [21][22][23] and well-studied [24][25][26] models is the Entering Mentoring (EM) curriculum [27,28]. These workshops focus on improving mentors' skills in six competency areas: maintaining effective communication, aligning expectations for the mentoring relationship, assessing mentees' understanding of research, addressing equity and diversity in mentoring relationships, fostering mentees' independence, and promoting mentees' professional development.…”
Section: Introductionmentioning
confidence: 99%